Occupational Health Procedure in Cooperatives of Recyclers of the Colombian Caribbean - Severiche - Sierra, Carlos; Barreto-Guerra, Deiry; Puello - Martínez , Ariel; Lugo - Calderon, Edgar; Ahumada - Villfañe, Irlena (Universidad Francisco de Paula Santander, 2023)
The general objective of the descriptive study was to review the occupational health procedures in cooperative associations of recyclers. This is a descriptive and applied research in the field, based on a non-experimental, cross-sectional design, taking as a sample a population of 100 recyclers belonging to the union of cooperatives in the Caribbean region of Colombia. The observation method was applied as an investigative technique and as an instrument a questionnaire was promoted for data collection, this was made up of different elements based on the Likert-style attitude scale, with five alternative answers. High compliance results were needed for integration, direction and diagnosis indicators, this indicates a positive trend to manage occupational health in recyclers unions grouped in cooperatives. It is observed, a medium level compliance in the security plan indicator and a weak infrastructure indicator, where the low dispersion of the data collected indicates coincidences in several answers, this reveals that the cooperative groups do not plan and the reason for this. failure is unknown